ENTREPRENEURIAL ORIENTATION, NETWORK RESOURCES, FIRM PERFORMANCE IN INDONESIAN ENTREPRENEURS' ASSOCIATION: THE MODERATOR EFFECT OF ENVIRONMENTAL DYNAMIC, SOCIAL AND BUSINESS NETWORK - Indriyani, Erlina Pipit; Lestari, Yetty Dwi; Suhariadi, Fendy (Jurnal Aplikasi Manajemen, 2023)
This study investigates the moderating effects of environmental dynamics, social networks, and business networks on the relationship between entrepreneurial orientation (EO) and firm performance. Through a questionnaire survey, 315 questionnaires were collected for analysis from managers and owners of businesses registered with KADIN, HIPMI, AKLI, GAPENSI, and REI Indonesia. This study made use of PLS-SEM analysis. Our results indicate that entrepreneurial orientation (EO) has a significant effect on business success and that network resources moderate this relationship. Moreover, our findings imply that environmental dynamics, social networks, and business networks augment the effect of entrepreneurial orientation (EO) on firm performance. The outcomes of this study add to both theory and practice. Theoretically, this study contributes to the body of knowledge and literature on how entrepreneurial orientation (EO) may enhance business performance via network resources following the concept of social capital that is influenced by a dynamic environment of social and commercial networks. This study can potentially improve corporate performance (EO) through strategic and entrepreneurial focus. The administration may employ this strategy to circumvent resource restrictions imposed by restricted access and a dearth of new opportunities. Therefore, Network resources enable enterprises to access additional resources, leading to a more successful EO implementation. In addition, environmental dynamics and social and business networks encourage the application of EO to enhance corporate performance.